Exercise at Different Ages and Appendicular Lean Mass and Strength in Later Life: Results From the Berlin Aging Study II. (5th October 2015) - Eibich, Peter; Buchmann, Nikolaus; Kroh, Martin; Wagner, Gert G.; Steinhagen-Thiessen, Elisabeth; Demuth, Ilja; Norman, Kristina
Abstract : Background: Excessive loss of muscle mass in advanced age is a major risk factor for decreased physical ability and falls. Physical activity and exercise training are typically recommended to maintain muscle mass and prevent weakness. How exercise in different stages of life relates to muscle mass, grip strength, and risk for weakness in later life is not well understood. Methods: Baseline data on 891 participants at least 60 years old from the Berlin Aging Study II (BASE-II) were analyzed. Linear and logistic regressions of self-reported exercise in early adulthood, old age, or both on appendicular lean mass (ALM), grip strength, and a risk indicator for weakness (ALM/ body mass index cutoff) were calculated. In addition, treatment bounds are analyzed to address potential confounding using a method proposed by Oster. Results: Analyses indicate that for men only, continuous exercise is significantly associated with higher muscle mass ( SD = 0.24, p < .001), grip strength ( SD = 0.18, p < .05), and lower risk for clinically relevant low muscle mass (odds ratio = 0.36, p < .01). Exercise in early adulthood alone is not significantly associated with muscle mass or strength. No significant associations were observed for women. Conclusions: The results of the current study underscore the importance of health programs to promote physical activity with a focus on young adults, a group known to be affected from environmentally associated decline of physical activity, and to promote the continuation of physical exercise from early adulthood into later life in general.